1977
DOI: 10.1042/bj1640305
|View full text |Cite
|
Sign up to set email alerts
|

The nature of controlled respiration and its relationship to protonmotive force and proton conductance in blowfly flight-muscle mitochondria

Abstract: 1. To determine whether controlled (State 4) pyruvate oxidation can support a high energy state, measurements of the redox span NAD-cytochrome c, phosphorylation potential and protonmotive force (the gradient in electrochemical activity of protons across the mitochondrial inner membrane) were made as indices of energy status. For comparison, these three measurements were also made with glycerol 3-phosphate, an alternative substrate. The two substrates gave essentially identical values for the redox span NAD-cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1978
1978
1988
1988

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…ATP synthesis in aerobic mitochondria and bacteria, or vesicles obtained from these organelles, is coupled to Δ/Ι Η depression (e.g., Nicholls, 1974;Sorgato et aL, 1978;Kell et aL, 1978a;Leiser and Gromet-Elhanan, 1977;Johnson and Hansford, 1977), and titrations confirm the close relationship between the rate of ATP synthesis and the extent of Δ/Ι Η depression . ATP synthesis in aerobic mitochondria and bacteria, or vesicles obtained from these organelles, is coupled to Δ/Ι Η depression (e.g., Nicholls, 1974;Sorgato et aL, 1978;Kell et aL, 1978a;Leiser and Gromet-Elhanan, 1977;Johnson and Hansford, 1977), and titrations confirm the close relationship between the rate of ATP synthesis and the extent of Δ/Ι Η depression .…”
Section: A In Favor I Aß H -Driven Atp Synthesismentioning
confidence: 80%
See 1 more Smart Citation
“…ATP synthesis in aerobic mitochondria and bacteria, or vesicles obtained from these organelles, is coupled to Δ/Ι Η depression (e.g., Nicholls, 1974;Sorgato et aL, 1978;Kell et aL, 1978a;Leiser and Gromet-Elhanan, 1977;Johnson and Hansford, 1977), and titrations confirm the close relationship between the rate of ATP synthesis and the extent of Δ/Ι Η depression . ATP synthesis in aerobic mitochondria and bacteria, or vesicles obtained from these organelles, is coupled to Δ/Ι Η depression (e.g., Nicholls, 1974;Sorgato et aL, 1978;Kell et aL, 1978a;Leiser and Gromet-Elhanan, 1977;Johnson and Hansford, 1977), and titrations confirm the close relationship between the rate of ATP synthesis and the extent of Δ/Ι Η depression .…”
Section: A In Favor I Aß H -Driven Atp Synthesismentioning
confidence: 80%
“…Similar conclusions have been drawn from double-inhibitor titration studies (Baum et al, 1971;Hitchens and Kell, 1982a;Westerhoff et al, 1982). Several reports contradict this (Padan and Rottenberg, 1973;Azzone et al, 1978c;Zoratti et al, 1981;Johnson and Hansford, 1977;Branca et al, 1981;Wilson and Forman, 1982;Sorgato et al, 1978;Holian and Wilson, 1980;see, however, Küster et al, 1981;Nicholls and Bernson, 1977;Nicholls, 1979), suggesting that ATP synthesis drains energy from the redox H + pump through a pathway which is not equivalent to Δ/Ι Η utilization for cation transport. The model proposes a stepwise activation of the ATPase depending on the number of H + ions interacting with the enzyme.…”
Section: B Againstmentioning
confidence: 99%
“…It seems to the reviewer that these experiments instead establish the role of the mitochondrion as providing ATP for some other membrane Ca 2÷ transport system, quite possibly in the endoplasmic reticulum. Oligomycin would not be expected to inhibit mitochondrial Ca 2+ uptake per se, as it does not diminish the driving force, ~0 , and indeed may even increase this quantity (Johnson and Hansford 1977). Oligomycin does, however, prevent mitochondrial synthesis of ATP.…”
Section: 2 Results Of the Direct Measurement Of Mitochondrial Ca Cmentioning
confidence: 97%
“…Spaces were calculated for each radioactive isotope (see above), giving the values c for methylamine, h for acetate and m for the matrix spaces respectively. By analogy with a previously described approach (Johnson & Hansford, 1977), an absolute value (N) was calculated for (h-c)/m. The magnitude of ApH was then given exactly by log [(N+V\N2+4)/2], and the sign of ApH depended on the sign of (h-c)/m: defining ApH as pHmedium-pHmatrjx, for (h-c)/m >0, ApH <0, and vice versa.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The effect of mitochondrial energy status on Si(OH)4 uptake was investigated by using a silicone-oil-centrifugation technique, since such a method has been shown to preserve mitochondrial energy states until complete separation of organelles from the suspending medium has been accomplished (Davis & Lumeng, 1975;Johnson & Hansford, 1977). Control experiments with rotenone-treated mitochondria showed that neither the silicone oil nor the dextran added to the medium (LaNoue et al, 1973) affected the results appreciably.…”
Section: Effects Of Si(oh)4 On Mitochondrial Respiration and Swellingmentioning
confidence: 99%